Development of an experimental test bench and a psychrometric model for assessing condensation on a low-pressure exhaust gas recirculation cooler. (May 2021) - Galindo, Jose; Navarro, Roberto; Tarí, Daniel; Moya, Francisco
A test bench has been designed to assess condensation formation produced on the interior of a low-pressure exhaust gas recirculation cooler working with hot stream of humid air representing an engine warm-up stage, when its coolant starts from very cold conditions. An experimental campaign has been conducted with three different exhaust gas recirculation mass flow rates, four exhaust gas recirculation inlet temperatures and three different coolant initial temperatures, covering common conditions found in the low-pressure exhaust gas recirculation system of internal combustion engines under cold starts. The transient experimental results are analyzed and compared with a simple psychrometric condensation model, obtaining a good correlation and reproducing the trends of the condensation, even though an overprediction of the condensates of around 20%–40% exists due to the strong hypotheses assumed. The warm-up tests are most sensitive to the initial coolant temperature. For example, an engine starting at –10 °C ambient temperature could require 10 min to stop producing water in the low-pressure exhaust gas recirculation cooler, with an accumulated quantity during the warm-up of about 100 mL of condensates.